2019
DOI: 10.21614/chirurgia.114.3.376
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Prognostic Significance of the Laboratory Risk Indicator for the Necrotizing Fasciitis (LRINEC) Score in Necrotizing Fasciitis

Abstract: Context: Discutăm despre rolul indicatorului de risc de laborator pentru fasceita necrozantă (LRINEC) asupra prognosticului acestei boli. Fasceita necrozantă (NF) se caracterizează prin răspândirea rapidă a infecţiei şi a necrozei ţesutului moale şi a fasciei. Metode: Treizeci de pacienţi (17 bărbaţi, 13 femei, vârsta medie 57,5 ani) au fost trataţi în perioada 2011-2016; au fost analizaţi retrospectiv în ceea ce priveşte vârsta, sexul, agenţii microbiologici izolaţi, modalităţile de tratament şi rata mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
8
1
Order By: Relevance
“…In one study, the mean cut-off value of the FGSI scores was determined to be 7.5 in mortality cases (10). In another study, the LRINEC score was found to be 9.2 in patients with a mortal course of FG, and 8.4 in patients who survived (20). The disease severity score in our study was mostly found to be lower than the data of advanced medical centers (9,10,12).…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…In one study, the mean cut-off value of the FGSI scores was determined to be 7.5 in mortality cases (10). In another study, the LRINEC score was found to be 9.2 in patients with a mortal course of FG, and 8.4 in patients who survived (20). The disease severity score in our study was mostly found to be lower than the data of advanced medical centers (9,10,12).…”
Section: Discussioncontrasting
confidence: 51%
“…They found that as the LRINEC score increased, the length of hospital stay increased. However, they determined the cut-off value as 6 and did not find a significant difference in the duration of hospitalization between groups (14 days vs. 21 days, p=0.21) (20). One study found that non-mortal FG patients with an FGSI score of 5.7 and a LRINEC score of 7.4 may have an extended hospital stay of 52 days (21).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition to them, significant comorbidities that affect the worsening of the prognosis are chronic renal failure, chronic heart disease, alcoholism, immunosuppression, systemic disorders, cirrhosis, local trauma, intravenous drug abuse, malnutrition, peripheral arterial disease [ 19 - 20 ]. In a study by Gonullu et al, more than half of the patients had at least one predisposing comorbidity and the most common (50%) comorbidity factor was diabetes mellitus [ 21 ]. Tarchouli et al reported an incidence of diabetes mellitus in 38% and cardiovascular diseases (high blood pressure, heart disease) in 51%, with a significantly higher mortality rate in heart disease [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tarchouli et al reported an incidence of diabetes mellitus in 38% and cardiovascular diseases (high blood pressure, heart disease) in 51%, with a significantly higher mortality rate in heart disease [ 22 ]. The effects of diabetes mellitus on mortality rate in NF is less clear, and several studies could not detect the correlation between mortality and DM [ 21 ]. In our study, DM occurs in 69%, obesity in 61%, high blood pressure in over 80%, heart disease in 46%, and chronic kidney disease (CKD) and malignancy in 15%.…”
Section: Discussionmentioning
confidence: 99%